Abbott Elementary. The complete second season [videorecording (DVD)] - Brunson, Quinta (Warner Bros. Entertainment, 2023)
The teachers are back at Willard R. Abbott Public School for development week, a time to prepare for the upcoming year before the students first day of school. Post-breakup, Janine is determined to start the year off right and leave her problems at home. Meanwhile, Ava runs a side hustle out of the school parking lot, and Gregory, now a full-time teacher, is in over his head with the curriculum.